Ответы и объяснения

2014-02-19T08:22:05+00:00
№ 1.
1) (х-8)(6-у)=6х-ху-48+8у
2) (3с+7)(4-3с)=12c-9c^2+28-21c=-9c^2-9c+28
3) (5a^2+)(3y-1)=15a^2 y-5a^2+3y-1
4) (x+3)(x^2-x-1)=x^3-x^2-x+3x^2-3x-3=x^3+2x^2-4x-3
5) 5(x+2)(x+3)=59x^2+5x+6)=5x^2+25x+30
6) (a+3)(b-7)=ab-7a+3b-21
7) (8+3x)(2y-1)=16y-8+6xy-3x
8) (3x^2-1)(2x+1)=6x^3=3x^2-2x-1
9) (5c-1)(c^2-5c+1)=5c^3-25c^2+5c-c^2+5c-1=5c^3-26c^2+10c-1
10) -8(y-1)(y+5)=-8(y^2+5y-y+5)=-8(y^2+4y+5)=-8y^2-32y-40
11) (x-4)(y+5)=xy+5x-4y-20
12) (5a-7)(3a+1)=15a^2+5a-21a-7=15a^2-16a-7
13) (5y^2-1)(3y^2-1)=15y^4-5y^2-3y^2+1=15y^4-8y^2+1
14) (7y-1)(y^2-5y+1)=7y^3-35y^2+7y-y^2+5y-1=7y^3-36y^2+12y-1
15) 3b(b-2)(2+4b)=3b(2b+4b^2-4+8b)=3b(4b^2+10b-4)=12b^3+30b^2-12b